In vivo evaluation of novel ketal-based oligosaccharides of hyaluronan micelles as multifunctional CD44 receptor-targeting and tumor pH-responsive carriers. (2nd April 2016) - Chen, Daquan; Sun, Jingfang; Sun, Kaoxiang; Liu, Wanhui; Wu, Zimei
Abstract : In this report, the oligosaccharides of hyaluronan (oHA)-histidine-menthone 1, 2-glycerol ketal (MGK) (oHM) carried pH-sensitive MGK as hydrophobic moieties and oHA as the target of the CD44 receptor. The oHM could self-assemble, with a diameter of 65 nm. The cellular uptake, indicated by the fluorescent signals, was higher at 4 h. The ex vivo imaging indicated that micelles have a longer blood circulation, beyond 5 h. The fluorescence intensity of the micelles in the liver and spleen was much higher from 5 to 24 h. The CD44 receptor-targeting, indicated by the fluorescence signals of A549 and MDA-MB-231 group, were higher than those of the HepG2 and the control.